IMPLEMENTATION OF BIMP-EAGA SUBREGIONAL COOPERATION WITH TRIANGLE ECONOMICGROWTH APPROACH FOR OVERCOMING FOOD CRISIS IN MINDANAO - Rara Gusnita Putri; Regiana Revilia (Faculty of Social and Political Sciences, Universitas Lampung, 2025)
Mindanao, Philippines, is now facing a food crisis triggered by hydrometeorological disasters (floods) and limited human resource capacity. Official Philippine government data recorded crop failures on 20,000 hectares of rice fields and 8,800 hectares of staple crops, threatening stability of the local food supply. This study analyzes the role of BIMP-EAGA (Brunei-Indonesia-Malaysia-Philippines East ASEAN Growth Area) subregional cooperation in crisis mitigation through the triangle economic growth approach. Using qualitative methods and policy analysis, the study examines three main mechanisms: (1) food security corridor as a commodity supply chain stabilizer, (2) farmer HR capacity building program based on agricultural technology transfer, and (3) agricultural infrastructure funding within the BIMP-EAGA Vision 2025 framework. Findings indicate that this collaboration significantly contributes to mitigating the impact of crop failure through regional food reserve schemes and cross-border trade facilities. However, implementation faces challenges due to domestic policy fragmentation and disparities in resource allocation. The study concludes that the effectiveness of BIMP-EAGA depends on the synergy of the economic growth triangle, especially in integrating climate adaptation, local community empowerment, and ASEAN policy harmonization.